An optimum design of high sensitivity PMMA-coated FBG sensor for temperature measurement - Dedi Irawan; Khaikal Ramadhan; Toto Saktioto; Azwir Marwin (Universitas Ahmad Dahlan, 2023)
Fiber Bragg grating (FBG) with silica material has limitations in measuring mechanical quantities such as strain and temperature, this happens because silica fibers are easy to break at higher transverse or axial strains. This deficiency can be overcome in several ways, one of which is by coating the silica FBG with a coating material made of metal or polymer. In this research, the FBG sensor has been designed by poly methyl methacrylate (PMMA)-coated FBG and silica. The finite element method (FEM) is used to analyze the electric field distribution on the surface of PMMA coated FBG with a coating thickness of 20 µm. Furthermore, the sensitivity of each coated FBG as a temperature sensor was measured in the range of 25 ℃ to 85 ℃ using coupled mode theory (CMT). From the design and analysis of coated FBG, it was found that FBG coated with PMMA material had the highest sensitivity of 395.73pm/℃. However, the FBG sensor coated with silica material has a sensitivity of 13.73 pm/℃. the shift obtained is also linear along with the temperature of 25 ℃ to 85 ℃.